DESIGN AS AESTHETIC PHENOMENON OF MODERN CULTURE - Abdullaeva, S.F (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
Studying the history of design, which reflects the main points of creativity, the development and dissemination of design that plays a specific place and role in modern society, is very important from the point of view of integrating its positive trends and ideas into modern culture. It is important to know the past of this field, to explore the possibilities of artistic creation, to determine its achievements and transfer them to the future. The modern era is a period of rapid development of culture, and during this period, to preserve national moral values, through a synthesis of traditional and non-traditional types of activity, it is necessary to carefully study these activities and make a clear idea of their history. The article says that design plays an important role in the life, development and emergence of certain areas of society. Therefore, the study of history, which reflects the main points of design, the path of its development and its distribution, is relevant. The study of positive trends and design ideas is an integral part of modern culture. Knowing the past of this field, exploring the possibilities of artistic creation, determining its achievements and translating it into the future is one of the problems highlighted in the article. It is noted that the formation of the national and spiritual values of Azerbaijan has come a long historical and cultural path, and it was influenced by many factors, both internal and external. This influence was manifested both in fashion and design, and in the formation of moral values. Having origins in ancient Turkic culture, Azerbaijani fashion and design form the aesthetic and philosophical structure of moral values and norms of various social institutions. One of the main issues in the history of culture of each nation is the consideration of measures in traditional modeling and design. Consideration of dimensionality plays an important role in the formation of concepts of national moral values, in the genesis of traditional ethics. Accounting measures give us an idea of the national roots and sources of design.